Development and evaluation of a rapid RPA/CRISPR-based detection of Francisella tularensis - Xu, Jian-Hao; Kang, Lin; Yuan, Bing; Feng, Zi-Han; Li, Shi-Qing; Wang, Jing; Wang, Ya-Ru; Xin, Wen-Wen; Gao, Shan; Li, Jia-Xin; Sun, Yan-Song; Wang, Jing-Lin; et al. (Frontiers in Microbiology, 2022)
Francisella tularensis is a dangerous pathogen that causes an extremely contagious zoonosis in humans named tularemia. Given its low-dose morbidity, potential to be fatal and aerosol spread, it is regarded as a severe public health threat. The US Centers for Disease Control and Prevention (CDC) have classified it as category A potential agent for bioterrorism and Tier 1 Select Agent. Herein, we combined RPA with CRISPR/Cas12a system to select the F. tularensis target gene (TUL4). creating a two-pronged rapid and ultrasensitive diagnostic methods for detecting F. tularensis. The real-time RPA assay detected F. tularensis within 10 min at a sensitivity of 5 copies/reaction, F. tularensis genomic DNA of 5 fg and F. tularensis of 2×102 CFU/mL; the RPA-CRISPR/Cas12a assay detects F. tularensis within 40 min at a sensitivity of 0.5 copies/reaction, F. tularensis genomic DNA of 1 fg, F. tularensis of 2 CFU/mL. Furthermore, the evaluation of specificity showed that both assays were highly specific to F. tularensis. More importantly, in a test of prepared simulated blood and sewage samples, the RT-RPA assay results were consistent with RT-PCR assay results, and the RPA-CRISPR/Cas12a assay could detect minute amounts of F. tularensis genomic DNA (2.5 fg). There were no non-specific detection with blood samples and sewage samples, giving the tests a high practical application value. For example, on-site and in epidemic areas, the RT-RPA was used for rapid screening and the RPA-CRISPR/Cas12a assay for more accurate diagnosis.